Multisensory Design in Bar Laurea - Karla Böhland (2011)
Nowadays importance of sense marketing is increasing because of too many visual and acoustic stimuli in our environment. Humans cannot pay attention to all these attractions. Bar Laurea considers this project as an opportunity to improve their image for students, visitors and Laurea staff. Advantage for Bar Laurea in having a multisensory design could be: having an innovative service concept which is well accepted in customers view and is a place where customers enjoying to stay. The amount of customers will increase and the income because customers prefer Bar Laurea instead other possibilities. This thesis is written about the internship-project “Multisensory Design in Bar Laurea” in Finland. The internship was held in the Sid Lab International at the Laurea University of Applied Science. Research had to be done about “Multisensory Design”, “Sense Market-ing” and “Neuromarketing”. Marketing research methods were used to create customer profiles of the target group and make a test lab observation. The main goal in the thesis was to find information’s about multisensory design and figure out which possibilities would be the best for Bar Laurea.
Keywords: sense marketing; multisensory design